Processing and characterization of sorghum protein concentrates using extrusion-enzyme liquefaction. - Stonestreet, Normell Jhoe de Mesa (Kansas State University, 2011)
Sorghum grain (Sorghum bicolor) is safe for consumption by individuals afflicted with celiac disease, and its proteins can be used as a supplement in gluten-free foods. However, utilization of sorghum in human foods is limited by the poor digestibility and lack of functionality of its proteins, which result from their entrapment in protein bodies, tight association with starch, and high degree of cross-linking induced by cooking. The first part of this study presents an extensive review of current methods for concentration and isolation of sorghum proteins, which are laboratory-scale techniques used for protein characterization and have no potential for commercial scale-up. Furthermore, these methods typically use non-food grade reagents and do not improve protein digestibility and functionality. In the second part, a novel extrusion-enzyme liquefaction (EEL) process was used to produce sorghum protein concentrates to overcome the aforementioned limitations. EEL involves extrusion pre-treatment of sorghum flour and starch liquefaction with a thermostable α-amylase, followed by enzyme inactivation, protein separation and drying. To demonstrate the concept, a laboratory-scale EEL process was used to produce concentrates with higher protein content (PC; 80% db) and digestibility (D; 74%) than those made by batch liquefaction. The optimum conditions for producing concentrates with both high PC and D were 32% wb in-barrel moisture content and 2.5% α-amylase added after extrusion. Using these conditions, EEL was scaled-up to a pilot-scale process to produce sorghum protein concentrates with 72-80% db PC and 62-74% D, while the batch liquefied control had only 70% db PC and 57% D. Dynamic oscillatory measurements of dough (55% moisture) and batter (65% moisture) containing sorghum protein concentrates (5 and 10%) and potato starch were performed to evaluate protein functionality. At lower moisture, pure potato starch and dough containing 10% sorghum protein concentrate had similar elastic and viscous moduli. At higher moisture, potato starch was more stable and exhibited significantly higher moduli than the batters with protein concentrates. Sorghum protein concentrates can improve the quality of some gluten-free foods. EEL shows promise for commercial production of sorghum protein concentrates because of its high throughput and potential for delivering high protein content and digestibility.
Keywords: Extrusion; Protein; Liquefaction; Sorghum; Gluten-free; Celiac; Food Science (0359)